Local-Sharia Regulations and Religious Expression in Aceh: Criticism of the Qanun about Establishing Places of Worship - Tobroni, Faiq (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2021)
Abstract: Religious identity-based laws can cause restrictions on the expression of religious freedom in the public sphere. It occurred in the implementation of Qanun Aceh 4/2016 about the provisions for establishing places of worship in Aceh (the Qanun). The enactment of the Qanun often triggers the majority hegemony over minority groups. Having focused on criticizing the Qanun, this article analyses two aspects. Firstly, the Qanun was reviewed from human rights. Secondly, the impact of the Qanun on the map on distribution and condition of places of worship for religious minorities in each regency/city in Aceh Province. This article uses qualitative research methods by utilizing, mapping, and reviewing data from the 2020 Central Statistics Agency of Aceh Province. This study found that: firstly, the Qanun does not meet the provisions of limitations on human rights in the 1945 Indonesian Constitution, International Covenant on Civil and Political Rights (ICCPR), and the Principle of Siracusa; secondly, the access for minority groups for establishing places of worship in Aceh can be mapped in three conditions, namely positive, normal and negative.Abstract: Hukum yang didasarkan pada identitas keagamaan bisa menyebabkan pembatasan ekspresi kebebasan beragama di muka umum. Ini terjadi dalam pelaksanaan Qanun Aceh 4/2016 tentang persyaratan pendirian tempat ibadah di Aceh (Qanun). Pemberlakuan Qanun sering memicu hegemoni mayoritas terhadap kelompok minoritas. Dengan fokus untuk mengkritisi Qanun, artikel ini mengulas dua aspek. Pertama, keberadaan Qanun ditinjau dengan Hak Asasi Manusian (HAM). Kedua, pengaruh Qanun terhadap peta distribusi dan konsisi tempat ibadah bagi kelompok keagamaan minoritas di setiap kabupaten/kota di Provinsi Aceh. Artikel ini menggunakan metode penelitian kualitatif dengan memanfaatkan, memetakan dan mereview data tahun 2020 dari Badan Pusat Statistik Provinsi Aceh. Penelitian ini menemukan: pertama, Qanun tidak memenuhi persyaratan pembatasan HAM yang diatur dalam UUD 1945, Kovenan Internasional Hak Sipil-Politik, dan PrinsipSiracusa; kedua, akses kelompok minoritas atas pendirian rumah ibadah di Aceh dapat dipetakan dalam tiga konidisi, yakni positif, normal dan negatif.